Chemical, Pharmacological, and in vitro Metabolic Stability Studies on Enantiomerically Pure RC‐33 Compounds: Promising Neuroprotective Agents Acting as σ1 Receptor Agonists. Issue 9 (5th July 2013) - Rossi, Daniela; Pedrali, Alice; Gaggeri, Raffaella; Marra, Annamaria; Pignataro, Luca; Laurini, Erik; Dal Col, Valentina; Fermeglia, Maurizio; Pricl, Sabrina; Schepmann, Dirk; Wünsch, Bernhard; Peviani, Marco; et al.
Abstract Our recent research efforts identified racemic RC‐33 as a potent and metabolically stable σ1 receptor agonist. Herein we describe the isolation of pure RC‐33 enantiomers by chiral chromatography, assignment of their absolute configuration, and in vitro biological studies in order to address the role of chirality in the biological activity of these compounds and their metabolic processing. The binding of enantiopure RC‐33 to the σ1 receptor was also investigated in silico by molecular dynamics simulations. Both RC‐33 enantiomers showed similar affinities for the σ1 receptor and appeared to be almost equally effective as σ1 receptor agonists. However, the R‐configured enantiomer showed higher in vitro hepatic metabolic stability in the presence of NADPH than the S enantiomer. Overall, the results presented herein led us to select (R)‐RC‐33 as the optimal candidate for further in vivo studies in an animal model of amyotrophic lateral sclerosis.